Leading Scholar Calls for Prompt Publication - Freedman, David Noel (The Biblical archaeology review, 1978)
How quickly should ancient texts be published after they come into a scholar’s hands? Within one year—at most, says Professor David Noel Freedman in a forthcoming issue of the Biblical Archaeologist.